Advanced strategies in immune modulation of cancer using lipid-based nanoparticles - Mizrahy, Shoshy; Hazan-Halevy, Inbal; Landesman-Milo, Dalit; Peer, Dan (Frontiers in Immunology, 2017)
Immunotherapy has a great potential in advancing cancer treatment especially in light of recent discoveries and therapeutic interventions that lead to complete response in specific subgroups of melanoma patients. By using the body’s own immune system it is possible not only to specifically target and eliminate cancer cells while leaving healthy cells unharmed, but also to elicit long-term protective response. Despite the promise, current immunotherapy is limited and fails in addressing all tumor types. This is probably due to the fact that a single treatment strategy is not sufficient in overcoming the complex anti-tumor immunity. The use of nanoparticle-based system for immunotherapy is a promising strategy that can simultaneously target multiple pathways with the same kinetics to enhance anti-tumor response. Here, we will highlight the recent advances in the field of cancer immunotherapy that utilize lipid-based nanoparticles as delivery vehicles and address the ongoing challenges and potential opportunities.